(untitled) (Research, Society and Development, 2022)
Objective: To assess adverse drug reaction (ADR) mortality and the distribution of deaths in Brazil and its regions. Methodology: Exploratory time series study of ADR mortality in Brazil by searching for data contained in the Mortality Information System-DATASUS, during the period of 2000-2019. The International Classification of Diseases, 10th revision (ICD-10) was resorted, codes Y40 to Y59. ADR mortality rates were calculated according to sex, age and region of residence. Results: In the 20 years that were analyzed, 2003 (0.001%) ADR deaths were registered. The average ADR mortality rate in Brazil was 0.0516/100,000, ranging from 0.0342 to 0.0715/100,000. The Southeast Region had the highest average mortality rates in the researched period, followed by the South and Midwest Regions, while the lowest rates were found in the North Region. The frequency of deaths were higher in women, having the highest rates in the age group of 60 years and over. Conclusion: ADR deaths rates are increasing in Brazil with regional differences. The small number of records in the period demonstrates the need of raising awareness among health professionals about filling out death certificates when the cause of it is related to ADR.